Effects of Reynolds number and layout on aerodynamic and heat transfer characteristics of an aluminum sheet treated in a gas-cushion furnace - Wu, Licheng; Kang, Can; Verdin, Patrick G.; Yin, Jin; Xie, Yu (Elsevier, 2025)
Heat treatment of an aluminum sheet through a gas-cushion furnace is numerically investigated. The sheet of 0.6 mm thick was suspended due to simultaneous impingement of upward and downward gas jets. Effects of Reynolds number (Re = 8,000–32,000) and upper/lower distance ratio (du/dl = 3:5, 1:1, 5:3) on flow and heat transfer characteristics were investigated, along with the structural characteristics of the sheet. The validation of the numerical results was implemented though experimental data. The results indicate that an increase in Re leads to an increase in circulating flow intensity in the gas-cushion furnace, due to an increase in the peak value of Nusselt number (Nu). However, the variation of Re imposes an insignificant effect on the pressure coefficient distribution over the sheet. At Re = 24,000, an upward deformation is evidenced at the middle part of the sheet. As Re decreases to 16,000, relatively slight downward deformation appears at the middle part of the sheet. At an upper/lower distance ratio of 3:5, a uniform pressure distribution is obtained at the lower surface of the sheet. Furthermore, the near-wall flow in the middle part of the sheet brings benefits, and such a layout is responsible for high average temperature of the sheet.
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 40 Engineering; 4017 Mechanical engineering; Gas-cushion furnace; Aluminum sheet; Deformation; Heat transfer; Reynolds number; Distance ratio